TDP-43 and FUS–structural insights into RNA recognition and self-association - Loughlin, Fionna E; Wilce, Jacqueline A (Current opinion in structural biology, 2019)
•Common and unique features influence RNA interaction and self-association by TDP-43 and FUS.•TDP-43 binds RNA sequence specifically whereas FUS binds both sequence and shape with limited specificity.•Prion-like domains of TDP-43 and FUS form reversible and irreversible aggregates.•Native oligomerization influences self-association of TDP-43.•Synergistic interactions between intrinsically disordered domains promote self-association of FUS. RNA-binding proteins TDP-43 and FUS play essential roles in pre-mRNA splicing, localization, granule formation and other aspects of RNA metabolism. Both proteins are implicated in neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Despite their apparent similarities, each protein has unique structural characteristics. Here we present the current structural understanding of RNA-binding and self-association mechanisms. Both globular and intrinsically disordered domains contribute to RNA binding, each with different specificities, affinities and kinetics. Self-associating Prion-like domains in each protein form multivalent interactions and labile cross-β structures. These interactions are modulated by distinctive additional domains including a globular oligomerization domain in TDP-43 and synergistic interactions with intrinsically disordered Arginine-Glycine rich domains in FUS. These insights contribute to a better understanding of native biological functions of TDP-43 and FUS and potential molecular pathways in neurodegenerative diseases.